Konseling Behavioral Teknik Relaksasi Afirmasi untuk Menurunkan Academic Burnout, Efektif Tidak? - Nur Rahmawati, Ajeng Intan; latifah, leny; Saidatun, Ica (Universitas PGRI Kanjuruhan Malang, 2023)
Academic burnout or academic fatigue is a condition experienced by individuals who feel excessive physical fatigue, experience boredom with academics and feel emotional exhaustion caused by the large number of tasks or responsibilities that are so heavy that the individual cannot complete all their responsibilities properly. GoodThe purpose of this research is to determine the effectiveness of behavioral group counseling services using affirmation relaxation techniques to reduce academic burnout. The method used in this research is quasi-experimental design. The technique used for sampling in this research is probability sampling. experimental results of behavioral group counseling services using effective affirmation relaxation techniques to reduce academic burnout.